Plano de projeto: implementação de um escritório de gerenciamento de projetos (PMO) no departamento da qualidade da empresa Alfa S/A - Roy, Felipe Centenaro (Universidade do Vale do Rio dos Sinos, 2015)
The object of this final paper is create a project planning to develop and structure a Project Management Office in the quality department at company ALFA S/A. The integration, scope, schedule, cost, quality, resources, communication, risk, procurement and stakeholders plans were developed and with them was possible define the projects’ demands to make the implementation and management of the project. The projects plans were done with base in the project management methodology and in accordance with good practice of Project Management Body of Knowledge (PMBOK) 5th Edition and the ten knowledge areas were covered. During plans’ project’s development were used technical and management tools as software MS Project, Gantt Chart, Critical Path, financial reserves, Curve "S", and others. The PMO has as main objectives improve the process of quality tasks in the organization's projects and define / control the conclusion of the minimum product quality requirements before market release. These activities will be administrated using tools, defining control methods, creating a departmental infrastructure and centralizing and standardizing information and documents.
Keywords: Plano de projeto; Escritório de projetos; PMO; Plano de gerenciamento do projeto; PMBOK; Project plan; Project office; Project management plan